2022
DOI: 10.32598/bcn.2021.1422.1
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitinase ABC Administration in Locomotion Recovery After Spinal Cord Injury: A Systematic Review and Meta-analysis

Abstract: Objective: The present systematic review and meta-analysis intends to conduct a comprehensive and complete search in electronic resources to investigate the role of administrating ChABC in improving complications following SCI. Methods: Medline, Embase, Scopus and Web of sciences were searched until the end of 2019. Two independent reviewers assessed the studies conducted on rats and mice and summarized the data. Using STATA 14.0 program, the findings were reported as pooled standardized mean differences (SMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Many pre-clinical articles have examined the effects of chABC injection on the improvement of functional recovery after SCI [58][59][60][61][62]. The results of a meta-analysis showed that the enzyme chABC injected alone had a moderate effect on the functional recovery post-SCI (SMD = 0.90; 95% CI 0.61 to 1.20; p < 0.001) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pre-clinical articles have examined the effects of chABC injection on the improvement of functional recovery after SCI [58][59][60][61][62]. The results of a meta-analysis showed that the enzyme chABC injected alone had a moderate effect on the functional recovery post-SCI (SMD = 0.90; 95% CI 0.61 to 1.20; p < 0.001) [40].…”
Section: Discussionmentioning
confidence: 99%
“…chABC also degrades the CSPGs that form perineuronal nets, thereby enhancing axonal sprouting and plasticity [37][38][39]. However, the use of chABC in animal models has problems that have caused the effect of chABC to be moderately reported in a metaanalysis study based on the results of 34 preclinical studies [40].…”
Section: Introductionmentioning
confidence: 99%
“…ChABC degrades the sulfated glycosaminoglycan side chains on CSPGs and improves functional outcomes in rodent models after SCI or TBI. [17][18][19] However, very specific sulfation patterns present in CSPGs play inhibitory roles in the CNS. Specifically, the CS-A sulfation pattern is neuroinhibitory while CS-C sulfation tends to be more permissive to axonal growth.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Following acute SCI, the first 24 h after injury are critical for achieving optimal neurological recovery with decompressive surgery. 22,23 Presently, there is ongoing debate regarding the prospective neurological benefits of durotomy. Smith et al 24 examined the recovery implications of durotomy with duroplasty in 72 rodents suffering from cervical SCI.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Following acute SCI, the first 24 h after injury are critical for achieving optimal neurological recovery with decompressive surgery. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%